EXPLORACIÓN DE HONGOS FILAMENTOSOS DE SUELOS DE PALMA CANARIA EN LA CIUDAD DE MÉXICO - lmaraz-Sánchez, Alejandra (2025)
The soils of Mexico City (CDMX) are heterogeneous, compact, with an alkaline pH, and with low microbiological diversity. In this context, the objective of the present study was to explore the diversity of filamentous fungi in Canarian palm soils with contrasting health conditions during the dry and rainy season 2022. 55 Canary Island palms with different health categories were sampled. From each one, soil was collected from two concentric rings and samples composed of each ring and each palm were formed, for which the pH and electrical conductivity were first determined. To know their fungal populations, the soil dilution technique in PDA-TS (potato-dextrose-agar-tergitol-streptomycin) culture medium was used. Identification was based on cultural and morphological characteristics. In the soils of the study area, a richness of seven fungal species was found, Aspergillus niger was the most abundant, representing 94.5% of the fungal community, while Fusarium oxysporum, Cladosporium cladosporioides, Nalanthamala vermoesenii, Paecilomyces lilacinus, Trichoderma harzianum, Penicillium sp., Mucor sp., and a dark mycelium fungus, represented the remaining 5.5%. A. niger, F. oxysporum, C. cladosporioides and Penicillium spp. showed variation according to the season. Regarding the health category of the palms, significant differences were only obtained for A. niger between the initial, intermediate, and advanced categories, while for A. flavus, the apparently healthy palms had lower population numbers than the intermediate ones. A. niger was the dominant species in the soils under study. For some fungi, differences were found regarding the sampling season. Although they were found in low quantity, other soil fungi are fulfilling various functions, from saprophytes and antagonists to phytopathogens. Regarding the health categories of palms, only A. niger and A. flavus showed significant differences in their populations. This is the first study of filamentous fungi in Canary Island date palm soils in Mexico City.